P-P30 Outcomes from resection of pancreatic metastases and non-neuroendocrine, non-pancreatic tumours. (16th December 2021) - Stevens, Claire; Chin, Sirr Ling; Karavios, Dimitrios; Takhar, Arjun; Arshad, Ali; Hamady, Zaed; Armstrong, Thomas; Pearce, Neil; Primrose, John
Abstract: Background: Isolated metastatic disease within the pancreas is an uncommon finding. The potentially higher perioperative risk and low incidence of resectable metastases has limited the development of evidence based guidelines for pancreatic metastectomy. However, reports in the literature suggest a considered approach to resecting patients with limited disease, favourable tumour type and a significant disease free interval. The aim of this study was to examine the indications and outcomes of pancreatic resection for metastatic disease and non-pancreatic, non-neuroendocrine malignancy at a high-volume pancreatic surgery centre. Methods: This is a retrospective analysis of a prospectively managed database of pancreatic resections for metastatic disease or primary non-pancreatic, non-neuroendocrine tumours at a single institution. Data collected and analysed included patient demographics, operative details and peri-operative outcomes, subsequent survival and mode of recurrence. Results: Records of 711 patients who underwent pancreatic resection were examined. 21 consecutive patients met the inclusion criteria, representing 3% of the unit's throughput. The perioperative morbidity and mortality were 33% and 0% respectively. Overall survival was 86months (95%CI 63-107) for renal cell carcinoma and 64months for other tumours. Conclusions: When coupled with the low morbidity and mortality rates of a high-volume pancreatic surgery centre using careful patient selection, pancreatic metastectomy has the potential to result in good long-term survival. Recent improvement in the efficacy of systemic therapies, particularly for renal cell carcinoma and melanoma contribute to the utility of resection and to the improved survival of patients.